(untitled) (Orfeu, 2021)
Abstract. From the works Cantiga e Danças dos pretos - for quartet of saxophones (1905) and ’Diálogo sonoro à luar’ - seresta for alto saxophone and bombardino in C, by Francisco Braga (S/D), in a succinct way, this article brings up the representativeness of the saxophone in Francisco Braga’s chamber repertoire. The text also argues about the composer’s pioneering and language when writing for the instrument and, as a result, presents, based on the studies by Oliveira (2019a) and Macedo (2019), significant aspects regarding Francisco Braga’s relations with the saxophone. In addition to observations on incongruous aspects regarding the composition date and other issues that permeate the ’Diálogo Sonoro ao Luar’, there are also notes on the stylistic interfaces between the influence Ars Gallica and the genres, seresta, maxixe and habanera, based on the studies by Nascimento (2009), Soares (2015) and Cazes (2019).